Association of α-Melanocyte–Stimulating Hormone With Corneal Endothelial Cell Survival During Oxidative Stress and Inflammation-Induced Cell Loss in Donor Tissue - Lužnik, Zala (JAMA Ophthalmol, 2020)
IMPORTANCE: Corneal endothelial cell (CEnC) damage and loss are major issues in eye banking and transplantation. The underlying mechanisms for CEnC loss are incompletely understood, and cytoprotective strategies that enhance CEnC viability could have a major effect on donor tissue quality and graft survival. OBJECTIVE: To investigate the cytoprotective role of neuropeptide α-melanocyte–stimulating hormone (α-MSH) in preventing CEnC loss in eye bank cold-stored corneas under oxidative and inflammatory cytokine-induced stress. DESIGN, SETTING, AND PARTICIPANTS: This single-center comparative research study conducted ex vivo experiments using 16 pairs of research-grade human donor corneas (courtesy of Eversight Eye Bank). Data were collected from June 2018 to November 2019, and data were analyzed from December 2019 to January 2020. EXPOSURES: Two corneas from the same donor were randomized to either control or 0.1 mmol/L of α-MSH treatment and then subjected to oxidative stress (1.4 mmol/L of hydrogen peroxide–phosphate-buffered saline for 15 minutes at 37 °C; n = 8 pairs) or cytokine-induced stress (100 ng/mL of tumor necrosis factor-α and 100 ng/mL of interferon γ for 18 hours at 37 °C; n = 8 pairs). Corneas were then stored at 4 °C. Specular images were taken at baseline and repeated twice per week using a calibrated wide-field specular microscope. CEnC viability was assessed using a fluorescent live/dead viability assay. MAIN OUTCOME AND MEASURES: Endothelial morphometry analysis, central corneal thickness measurements, and percentage of dead cells at day 11. RESULTS: Of 16 donors who provided corneas, 9 (56%) were male, and the mean (SD) age was 57.9 (12.4) years. Corneas were paired, and baseline parameters were comparable between all groups. At all time points, CEnC loss was lower in the α-MSH groups compared with the control groups. This difference was statistically significant after cytokine-induced stress (20.2% vs 35.2%; sample estimate of median, −14.9; 95% CI, −23.6 to −6.3; P = .008). Compared with the control group, α-MSH treatment resulted in a smaller increase in central corneal thickness (cytokine-induced stress: 89.3 μm vs 169.8 μm; sample estimate of median, −84.9; 95% CI, −131.5 to −41.6; P = .008; oxidative stress: 43.6 μm vs 111.9 μm; sample estimate of median, −68.8; 95% CI, −100.0 to −34.5; P = .008) and a smaller proportion of cell death (cytokine-induced stress: 2.7% vs 10.4%; difference, −7.7; 95% CI, −13.1 to −2.4; P = .01; oxidative stress: 2.9% vs 12.4%; difference, 9.5; 95% CI, 5.1 to 13.9; P = .006). CONCLUSIONS AND RELEVANCE: In this study, α-MSH treatment attenuated CEnC loss during cold storage after acute oxidative and cytokine-induced stress in human eye bank cold-stored corneas. These data suggest that supplementation of corneal storage solution with α-MSH may positively affect CEnC survival after transplant and protect the endothelium from proinflammatory cytokines and oxidative stress after full-thickness or endothelial keratoplasty, which is particularly valuable in patients at high risk of graft failure.